2018
DOI: 10.1088/1361-6579/aaa1d3
|View full text |Cite
|
Sign up to set email alerts
|

Reference intervals for the evoked tympanic membrane displacement measurement: a non-invasive measure of intracranial pressure

Abstract: We present the largest dataset of evoked TMD in healthy individuals and the first set of RIs for V . A patient cohort with both invasive ICP and evoked TMD measurements is needed to validate the technique for clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…It is possible therefore that the difference is within the bounds of statistical variations. It does however support a similar left to right difference observed in evoked TM displacement in the supine position [4] . The results suggest that an anatomical difference may exist between left and right ears.…”
Section: Discussionsupporting
confidence: 58%
“…It is possible therefore that the difference is within the bounds of statistical variations. It does however support a similar left to right difference observed in evoked TM displacement in the supine position [4] . The results suggest that an anatomical difference may exist between left and right ears.…”
Section: Discussionsupporting
confidence: 58%
“…The status of the cochlear aqueduct was unknown in the patients we tested. Studies using postural changes and evoked TMD indicated at least 81% of normal healthy subjects of this age range have a patent cochlear aqueduct in at least one ear and that for an individual ear, between 63% and 71% of cochlear aqueducts are patent (Campbell-Bell et al, 2017). This would imply that between 3 and 4 out of 11 of our patients may have had occluded cochlear aqueducts in the ear tested.…”
Section: Discussionmentioning
confidence: 75%
“…Macrae et al found that acoustic impedance at the TM was raised in living human subjects when intracranial pressure increased 9 . Tympanic membrane displacement could be used to evaluate intracranial pressure 10,11 …”
Section: Introductionmentioning
confidence: 99%
“…9 Tympanic membrane displacement could be used to evaluate intracranial pressure. 10,11 Compared to the measurements described above, wideband absorbance immittance (WAI) has a wider range of stimulation frequencies, between 226 and 8000 Hz, which can provide more information about the middle and inner ear status in terms of acoustic energy absorbance (EA) across different frequencies at different pressures. Because of its rapid and noninvasive nature, WAI has been used as a sensitive diagnostic tool for the assessment of middle ear conditions in ENT and Audiology clinics.…”
mentioning
confidence: 99%